STUDI ETNOGRAFI PERILAKU PENGEMIS MASYARAKAT DESA PRAGAAN DAYA KABUPATEN SUMENEP - Rina Hardiyantina; Sukardi Sukardi (Publisia: Jurnal Ilmu Administrasi Publik, 2016)
Pragaan Daya village in Sumenep Regency is known as the village of beggars, for begging into people's daily work. Which became the main motive for people to do the work of begging is behavior "beg" hereditary so as to form a local cultural entities. In addition, the quality of human resources is still low which can result mindset people less creative and view life narrowly. Begging that can not be eliminated from Pragaan Daya vilagers be the reason why this work is still occupied them hereditary. Sumenep regency government has sought to address the begging behavior in their communities through the local legislation, the implementation of local government a persuasive approach to coaching, empowerment. Nonetheless, the fact that there are showing people in the hamlet village of Nong Pote vilages in Pragaan Daya still begging activity.DOI: https://doi.org/10.26905/pjiap.v1i1.428